The factor structure of cognitive reflection, numeracy, and fluid intelligence: The evidence from the Polish adaptation of the Verbal CRT. (22nd August 2022) - Sobkow, Agata; Olszewska, Angelika; Sirota, Miroslav
Abstract: The Cognitive Reflection Test (CRT) is one of the most popular measures of individual differences in rational thought and decision making. To overcome the issue of overlap with numeracy, a novel measure of cognitive reflection less related to numeracy and math anxiety than Numerical CRT was developed—Verbal CRT. The present research had two main aims: first to investigate the generalizability of Verbal CRT in cultural contexts outside the United States/United Kingdom and second to test the factor structure linking traditional—numerical—CRT, Verbal CRT, numeracy, and fluid intelligence. In Studies 1a and 1b, we adapted and tested the validity and psychometric properties of Polish versions of tasks and scales. Next, using a large and diverse sample of Polish adults, we tested five models of the factor structure of cognitive abilities and thinking dispositions (Study 2). The most parsimonious and best‐fitted model contained three latent variables: Verbal CRT, numeracy (composed of the items from the Berlin Numeracy Test and traditional—numerical—CRT), and fluid intelligence. In line with previous research, our results show that Verbal CRT is a valid cognitive reflection measure that provides a clearer interpretation than traditional CRT, even in a different language and cultural context.